Perancangan Desain Website Adens Gaming dengan menggunakan Metode Design Thinking - Kevin Naphan Dwiputra; Diah Priharsari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Adenscorp is a small enterprise based in city of Malang, West Java that provides social media managemend services, brand awareness improvement, and also talent agency. In addition, Adenscorp is planning to expand their market by held a game tournament that was originally planned to be held twice a year. In addition to support the event, Adenscorp need a website to build an trusts of the player candidates of the tourney and to increase the quality of the technical matters. While developing the website's design of Adens Gaming, there is a problem that was expressed by the owner that did not have a deep understanding of the needs of the player candidates of the website that will be develop. In this research, the method of design thinking was used as the approach to find a deeper understanding of the problem and also to find the solution to a deeper understanding of the user's needs. On the process of developing the website, emphatize was done in a way of doing user interview to the targeted user that was done by interviewed Adenscorp as the stackholder. Formulation idea solutions or ideate using information achitecture and user flow. The outcome of this research is in the form of high-fidelity prototype design. The prototype was examined using usability testing method with the results are 94,2% on the effectiveness, 93,1% efficiency, and the average 85 on the satisfaction.